Faktor-Faktor Yang Berhubungan Dengan Status Karies Gigi Pada Anak Sekolah Min 1 Kota Banjarmasin - Astannudin syah; Rizqi Aulia Ruwanda; Abdul Basid (HB PRESS, 2019)
Background of the study: At the age of 10 and over, 71,2% of children experience dental caries. The prevalence of active caries in Kota Banjarmasin is 65%. While in Puskesmas (Public health service) Kelayan Timur working area, 389 cases of dental caries found. Additionaly, the governement through Kemen-Kes RI (Indonesian Health Ministry) tergeting Indonesian society to be free from dental caries by 2030. Some factors influencing dental caries are dental health awareness and attitudes namely time and frequency of brushing teeth, cariogenic foods, and the method of brushing teeth. Purpose of the study: this study is aimed to reveal the correlation between knowledge factors as well as dental health attitudes and dental caries status. Methods: This is an anlytical study utilizing cross sectional. The sample of the study is students of MIN 1 Kota Banjarmasin in 2018 with the total of 53, taken by means of perposive sampling. Statistical testing used is chi-square with 95% of reliance degree. Result of the study: The result shows that there are correlations between dental health knowledge p-value 0,004, time and frequency of brushing teeth p-value 0,002, cariogenic foods p-value 0,018, as well as teeth brush method p-value 0,015 and dental caries occasion in MIN 1 Kota Banjarmasin. Conclusion: The dental caries status is affected by dental health knowledge and attitudes.